Penerapan Model Utaut (Unified Theory Of Acceptance And Use Of Technology) Untuk Memahami Niat Dan Perilaku Aktual Pengguna Go-Pay Di Kota Padang - Mutiara Indah; Henri Agustin (Universitas Negeri Padang, 2019)
This study aims to find evidence that the model UTAUT (Unified Theory of Acceptance and Use of Technology) is a conceptual framework to explain the acceptance and use of Go-Pay as one of the mobile payment services in the city of Padang. The data used in this research is primary data obtained by distributing a questionnaire online. This study using purposive sampling with a sample of 150 respondents who have used Go-Pay.Analysis of the data used in this research is Structural Equation Modeling (SEM). Data analysis techniques using SmartPLS ver.3.2.8 processed. This study found evidence that performance expectancy, social influence and positive effect on behavioral intention; facilitating condition and behavioral intention to use behavior has a positive effect, while the effort expectancy negatively affect behavior intention.